PREVALENCE OF CYBERCHONDRIA AND ITS RELATION TO HEALTH ANXIETY AMONG PHYSICAL THERAPY STUDENTS IN KARACHI, PAKISTAN: A CROSS-SECTIONAL STUDY (The Research of Medical Science Review, 2025)
Introduction: The growing dependency on the internet for retrieving health-related information is thought to elevate anxiety levels and induce cyberchondria. Around 60% to 80% of internet users search for health information online. Students may be particularly susceptible to cyberchondria because of their easy access to medical information and resources. Objectives: The study aimed to identify the prevalence of cyberchondria among physical therapy students and examine its relationship with health anxiety. Methods: This cross-sectional study used convenience sampling to select physical therapy students from institutes in Karachi, Pakistan. Eligible participants were aged 18- 25 years and enrolled in a physical therapy program. Students with diagnosed mental health issues, or taking psychiatric medications were excluded. Data was collected through online surveys and hard copy questionnaires. Cyberchondria was assessed through CSSS and health anxiety by using SHAI. The data analysis was done using SPSS 21.0. Results: The mean age of the participants was 21.12 years (SD ±1.666). Out of 614 participants 491 were female and 122 were male. Most participants (531) showed moderate levels of cyberchondria, while 74 had severe and 9 had mild levels. A significant positive relationship was seen between cyberchondria and health anxiety with Pearson correlation coefficient 0.205 (p<0.01). Conclusion: Awareness campaigns should be established to educate students about the dangers of excessive internet health searches, and mental health resources should be made available.